Using Eye Tracking Technology in the Neuromarketing Research - Mital Olena H. (Bìznes Inform, 2020)
The article aimed at researching the benefits of eye-tracking technology in terms of the market research, product promotion and pricing strategy. The important potentials of using eye tracking technology in the practical marketing activities such as branding, segmentation, product development, pricing solutions, placement strategies, advertising solutions and social marketing are examined. The term «eye tracking» as it is used in neuromarketing means assessing the direction of the user’s gaze. The main area of its commercial application was the study of the perception of the composition of newspaper strips and magazines, design and packaging of products. With the spread of the Internet and the entry of companies into the network space, eye tracking has received a new round of development associated with the study of the perception of websites. Tracking the direction of the consumer’s gaze in the market research can give an idea of the consumers’ habits, even if those consumers do not know that they are being watched. The research using eye tracking technology can help developing new products, improving consumer segmentation, and choosing a good pricing policy. It is displayed that there is a wide range of possibilities of using eye tracking methods in both neuromarketing and market research. A conclusion is drawn that neuromarketing and its eye tracking technology are becoming increasingly popular both in academia and in the business world.